Multimedia-Based Mathematics Teaching Materials for Eighth Grade Students at SMP Negeri 1 Dua Boccoe, Bone Regency - Maghfirah, Fatwa Ridha; Rusli, Rusli; Rahman, Abdul; Musa, Hastuty (PT ARRUS Intelektual Indonesia, 2025)
The purpose of this study is to create multimedia-based teaching resources on quadrilaterals for eighth-grade students at SMP Negeri 1 Dua Boccoe. Research and development (R&D) is the methodology employed, and the ADDIE development model serves as the basis for the procedures. One math instructor, twenty-five eighth-grade students from SMP Negeri 1 Dua Boccoe, as well as media and content specialists, are the research subjects. In order to ascertain the practicality of the teaching materials in terms of learning quality, interest, and student independent learning, the following research instruments were used: (1) a material validation sheet by content experts, which aimed to assess the material content's suitability with the curriculum and learning objectives; (2) a material validation sheet by media experts, which aimed to assess the appearance, design, and feasibility of the multimedia used; and (3) a teacher response questionnaire. According to the study's findings, the instructional materials were deemed legitimate after being evaluated by media experts with a 95% approval rate and content experts with a 96% approval rate. Furthermore, based on the results of the teacher and student questionnaires, which covered ease, interest, and autonomous learning, the teaching materials were deemed practical with a 94% and 93% percentage, respectively. As a result, the multimedia-based teaching resources for mathematics for Class VIII pupils are deemed appropriate, fulfilling the requirements of being legitimate and useful for teaching the subject of quadrilaterals.